DAMPAK PENGGUNAAN APLIKASI PEMBELAJARAN BERBASIS PERMAINAN TERHADAP KEMANDIRIAN BELAJAR SISWA KELAS TINGGI DI SDN 6 TANJUNG BATU - Rahayu, Sasti; El Cintami Lanos, Muhsana; Hermansah, Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to reveal how the use of Interactive Educational Applications, which are game-based learning media, affects the learning independence of high-grade students at SDN 6 Tanjung Batu. The focus of this study was on grade V.B students, with six students as subjects selected purposively. The method used was a descriptive qualitative approach, with data collection through observation, interviews, and documentation. The results showed that the use of this application had a positive effect on students' learning independence. It was seen that students became more enthusiastic in learning, more independent in managing their time, and had higher initiative in completing assignments without depending on teachers. The game features in the application also helped create a more enjoyable and interesting learning atmosphere for students. However, several challenges were also found, such as the need for adjustment time when initially using the application and impaired focus due to overly dominant game elements. Overall, Interactive Educational Applications have great potential to support independent learning, especially if implemented with appropriate supervision and guidance from teachers.